Evaluation of antibiotic utilization pattern in indoor patients of obstetrics and gynaecology in a tertiary care hospital of central India - Kumawat, Shrutika; Dudhgaonkar, Sujata; Uike, Pravin (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Understanding prescribing patterns is vital to address irrational antibiotic use, a key contributor to antimicrobial resistance. The aim of the study was to evaluate antibiotic prescription practices among hospitalized patients and examine the presence of an antibiotic stewardship program in a tertiary care hospital. The findings may aid in developing stewardship initiatives to promote rational antibiotic use. Methods: A prospective observational study was conducted from March 1 to August 30, 2024, at Government Medical College and Hospital, Gondia, Maharashtra. Data were collected using WHO prescribing drug indicators and analysed using SPSS Version 25. Results: The mean difference in final and initial serum creatinine values were observed to be 0.32 and 0.52 with a standard deviation of 0.228 and 0.387 in AM and GM group respectively. This difference was statistically significant with p value of 0.007. The mean difference in final and initial creatinine clearance values were observed to be 18.82 and 24.76 with a standard deviation of 10.14 and 11.93 in AM and GM group respectively. This difference was also statistically significant with p value of 0.013. Nephrotoxicity occurred in 9 out of 50 patients (18%) in AM group out of which 12% were male and 6% were female whereas in case of GM group nephrotoxicity occurred in 16 out of 50 patients (32%) in which 26% were male and 6% were female. Conclusions: Prescribing patterns deviated from WHO indicators, with high empirical use. Strengthening antimicrobial stewardship and increasing microbiological testing are essential to improve antibiotic practices.